Necrotizing Urethritis due to Aerococcus urinae - Abdulrahman A. Babaeer; Claudia Nader; Vito Iacoviello; Kevin Tomera (Case Reports in Urology)
A 49-year-old male presented to the emergency with hematuria and pain in the shaft of the penis for one day. The patient was found to be in a state of shock. The shaft of the penis and the scrotum were swollen and tender. No skin necrosis was observed and no crepitus was palpable. Serum white count (WBC) was 29.5 × 103/μL. A CT scan showed gas in the corpus spongiosum. Antibiotics were started with IV metronidazole, vancomycin, and piperacillin/tazobactam. Metronidazole was then replaced by clindamycin. Exploration was performed but no necrotic tissue was identified. Cystourethroscopy revealed dusky looking urethra. A suprapubic tube and a urethral catheter were placed in the bladder. WBC trended down to 13.9 × 103/μL on the fourth postoperative day. Urine culture grew Aerococcus urinae and blood cultures grew Alpha Hemolytic Streptococcus. On the sixth day, the patient was feeling worse and WBC increased. MRI revealed absent blood flow to the corpus spongiosum. Urethroscopy revealed necrosis of the urethra. Urethrectomy was performed via perineal approach. The patient immediately improved. The patient was discharged on the sixth postoperative day to continue ampicillin/sulbactam IV every 6 hours for a total of 4 weeks from the day of urethrectomy.